Evaluation Of The Capability of Gas Producer Tools Using a Combination Of QFD and MCDM - Rizbudipriyana, Andhika Luthfi; Rezalti, Dian Tiara; Kurniawan, V Reza Bayu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The LPG gas base carries gas to homes and shops using a two-wheeled motorcycle fitted with an iron basket to have gas. A design needs to be designed to make it easier to transport gas. This study aims to determine the weight of criteria that are important for consideration of design design for a gas conveyor. Quality Function Deployment (QFD) is a structured methodology used in product planning and development to obtain consumer needs and wishes specifications. Multi-Criteria Decision Making (MCDM) is a method for making alternative decisions based on specific criteria. The result of this study is the weighting of measures necessary for consideration of design for a gas conveyor of the most crucial sequence, namely: type of material used, weight, strength, size and dimensions, flexibility, maximum capacity, durability, comfort, attractive graphic design, efficiency (gallons, gas 3kg, 5.5kg, 12kg), and thickness